Evaluation of the Antibacterial Effect of Propolis Extract and its Use in Mouthwash Production - Rahman Nazeri; Marzieh Ghaiour; Shima Abbasi (Tehran University of Medical Sciences, 2019)
Objectives: The purpose was to determine the antibacterial properties of propolis and to evaluate its use as an antibacterial mouthwash with minimal complications Materials and Methods: In this experimental laboratorial study, the alcoholic extract of Propolis was first prepared. Then the Minimum Inhibitory Consentration(MIC) was calculated for four bacterial species of staphylococcus aureus, Streptococcus mutans, Lactobacillus acidophilus and Enterococcus faecalis using the agar dilution test. Using the MIC, the Propolis antibacterial mouthwas was produced and compared to water, chlorhexidine and Listerine in laboratory rats for clinical examination. Salivary specimens of rats were collected 12 hours, 1 week and 2 weeks after using the mouthwash and examined by the real time PCR. Data were analyzed by SPSS using one-way ANOVA and the independent t-test (α=0.05). Results: The results of agar dilution test showed the lowest MIC for Staphylococcus aureus and the highest for Lactobacillus acidophilus. On the other hand, the results of this study showed that water alone had no effect on the level of oral bacteria. In the case of Streptococcus mutans, Enterococcus faecalis, and Lactobacillus Acidophilus mouthwash, the Propolis mouthwash showed a significant difference with chlorhexidine and listerine (P <0.05), while chlorhexidine and listerine had lower effect in comparison. As for Staphylococcus aureus, there was no significant difference between chlorhexidine and Propolis bacteria (P >0.05), but Listerine had the lower effect than either (P <0.05). Conclusions: According to the results, propolis mouthwash was more efficient against the studied oral bacteria compared to CHX and Listerine.